Work-Specific Digital Competencies of HR Managers - Bernik, Nejc; Šprajc, Polona (Organizacija in organiziranje, 2025)
The research addresses the crucial role of HR managers in modern organizations, emphasizing the importance of their digital competencies. As organizations strive for success in a competitive market, it is essential for HR managers to master digital tools and technologies. Digital literacy, proficiency in information and communication technology (ICT), and artificial intelligence are becoming necessary elements for the effective management of HR processes. The research examines tools suitable for measuring the job-specific digital competencies of HR managers. For the purpose of evaluating the job-specific digital competencies of HR managers, we reviewed, adapted, and developed a competency matrix and a table of key performance indicators (KPIs). Based on a SWOT analysis, we selected the most appropriate tool for assessing the job-specific digital competencies of HR managers.